Formation of an emergent protestor identity: Applying the EMSICA to the Gezi Park protests. (February 2022) - Uysal, Mete Sefa; Akfırat, Serap Arslan
Recent research on collective action indicates the importance of dynamic and culturally diverse perspectives. One of these models, the encapsulated model of social identity in collective action (EMSICA), claims that perceived injustice and group efficacy shape the emergence of novel forms of identity during protests. An emergent social identity is a strong predictor of collective action participation, as recent studies have demonstrated. In this study we aim to test the tenets of the EMSICA in a non-WEIRD context, the Gezi Park protests in Turkey. We conducted a retrospective survey study with 345 activists who participated in the Gezi Park protests. Findings showed that increased perception of injustice of the government's totalitarian policies, the decision to demolish Gezi Park, police brutality, as well as group efficacy beliefs predicted the Gezi Park protestor identity. Moreover, the emergent Gezi Park protestor identity directly predicted participation in the protests. Our findings highlight that the EMSICA has important predictive power in a non-WEIRD context, the Gezi Park protests, and showed that perceived injustices and group efficacy became facilitators of the emergence of an overarching protestor identity. We believe that the core drivers of collective action should be understood and tested as context-sensitive, and we should extend our understanding about core motivations from global categories to contextual outcomes of intergroup encounters. In conclusion, we hope this study pave the way for understanding dynamics of collective action participation in repressive contexts, demonstrating how injustices such as totalitarian policies and police brutality along with group efficacy become facilitators of the emergence of an overarching protestor identity.